The art of survival between the religious and the aesthetic in the communist prisons in Romania. „Diary of Happiness” by Nicolae Steinhardt - Ivancu, Emilia (Balcanica Posnaniensia. Acta et studia, 2010)
This study explores the intersection between religion, art, and survival in Nicolae Steinhardt’s Diary of Happiness, a unique autobiographical work written in the aftermath of his imprisonment under the Communist regime in Romania. The paper situates Steinhardt’s diary within the broader context of Romanian memorialistic literature that emerged after 1945 as a form of moral resistance and spiritual survival in a time of political repression and cultural censorship. Drawing on literary criticism and historical sources, the analysis traces how Steinhardt – an intellectual of Jewish origin who converted to Christianity during his incarceration – transforms the experience of suffering into an aesthetic and spiritual journey of redemption. The research employs textual and comparative analysis, focusing on the diary’s narrative structure, confessional tone, and interplay between religious and artistic codes. Steinhardt’s reflections are examined in relation to the Christian tradition of autobiographical confession, as exemplified by Saint Augustine, as well as to modern theories of self-writing. Through close reading, the paper demonstrates how „Diary of Happiness” transcends the limits of political testimony, becoming both an act of faith and a work of art. The study concludes that Steinhardt’s text redefines the meaning of freedom, identity, and salvation under totalitarian oppression. By integrating aesthetic contemplation with Christian ethics, the author creates a „spiritual art of survival” where the act of writing itself becomes redemptive. His diary thus stands as a testimony to the resilience of the human spirit and the transformative power of belief and creativity in the face of absolute suffering.